2003
DOI: 10.1115/1.1610020
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic Pressurization and Depletion of Trapped Lubricant Pool During Creep Contact of a Rippled Indenter Against a Biphasic Articular Cartilage Layer

Abstract: This study presents an analysis of the contact of a rippled rigid impermeable indenter against a cartilage layer, which represents a first simulation of the contact of rough cartilage surfaces with lubricant entrapment. Cartilage was modeled with the biphasic theory for hydrated soft tissues, to account for fluid flow into or out of the lubricant pool. The findings of this study demonstrate that under contact creep, the trapped lubricant pool gets depleted within a time period on the order of seconds or minute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 39 publications
1
23
0
1
Order By: Relevance
“…In addition, models have shown that the highly porous nature of cartilage at its surface is capable of maintaining effective lubrication even in the absence of weeping flow, as only about 1% of the total contact area of cartilage layer interactions consists of solid-solid contacts, where friction occurs. 151 Therefore, the initial friction coefficient following an applied load is decreased by trapped lubricant at the surface, independent of squeeze-film lubrication effects. 151 However, it has been suggested that although compressive stresses prevent the initiation of fissures in a healthy joint, that normal movements in a pathological joint with a thin synovial fluid layer can easily cause fissures.…”
Section: Microscopic Roughness Of the Articular Surfacesmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, models have shown that the highly porous nature of cartilage at its surface is capable of maintaining effective lubrication even in the absence of weeping flow, as only about 1% of the total contact area of cartilage layer interactions consists of solid-solid contacts, where friction occurs. 151 Therefore, the initial friction coefficient following an applied load is decreased by trapped lubricant at the surface, independent of squeeze-film lubrication effects. 151 However, it has been suggested that although compressive stresses prevent the initiation of fissures in a healthy joint, that normal movements in a pathological joint with a thin synovial fluid layer can easily cause fissures.…”
Section: Microscopic Roughness Of the Articular Surfacesmentioning
confidence: 98%
“…151 Therefore, the initial friction coefficient following an applied load is decreased by trapped lubricant at the surface, independent of squeeze-film lubrication effects. 151 However, it has been suggested that although compressive stresses prevent the initiation of fissures in a healthy joint, that normal movements in a pathological joint with a thin synovial fluid layer can easily cause fissures. 82 A classic overview of surface characteristics of articular cartilage was presented in the mid 1970s.…”
Section: Microscopic Roughness Of the Articular Surfacesmentioning
confidence: 98%
“…Articular cartilage is a multiphase material consisting of a fluid phase comprising 60-85% of the tissue wet weight (ww) Forster and Fisher, 1996) and a solid phase mainly composed of collagen ( 15-30% ww) and proteoglycans ( 4-7% ww) . Water and lubricant pools form between asperity microcontacts of loaded articular cartilage (Soltz et al, 2003). Various mechanisms responsible for the development of trapped lubricants have been proposed, including weeping (Lewis and McCutchen, 1959), boosted (Walker et al, 1968), and squeeze film mechanisms (Hou et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Although interstitial fluid pressurization contributes to joint lubrication in mammals (27), lubricin has been established as a very important factor in maintaining low values in diarthrodial joints. Previous research using Prg4-null mice indicated that joints from homozygotes had significantly higher values compared with those from either heterozygotes or normal mice (28).…”
mentioning
confidence: 99%